The Sion revelation the truth about the guardians of Christs's sacred bloodline - Picknett, Lynn; Prince, Clive (New York, NY Touchstone, a trademark of Simon & Schuster, Inc., 2006)
Explores the mysterious Priory of Sion organization, investigating key questions about the alleged descendants of Jesus and Mary Magdalene, Leonardo da Vinci's possible membership, and the identity of Grand Master Pierre Plantard.
Chapter 1 True Liesp -- Chapter 2 Behind the Thronep -- Chapter 3 A Tale of Two Treasuresp -- Chapter 4 "Hidden Gold, Hidden Blood" -- Chapter 5 The Bloodline Mythp -- Chapter 6 Return to the Sourcep -- Chapter 7 The Shape-Shiftersp --Chapter 8 A New United States.
"A Touchstone book."
Includes bibliographical references and index.
Keywords: Jesus Christ -- Cult; Mary Magdalene -- Saint -- Cult; Prieuré de Sion; Secret societies -- France; Secret societies -- Religious aspects -- Christianity